Evaluation of Physical Environmental Conditions in Unplanned Settlements Towards Eco-Settlement - N L Azqiyah; D Nurgandarum; K Lahji (Talenta Publisher, 2025)
Urban unplanned settlements have important function dan potential to be developed into a self-help-based urban eco-settlement. The quality of eco-settlement as sustainable settlements refers to friendly city with its equity, accessibility of the physical environment, and inclusiveness of the social environment. Using evaluation of physical environmental conditions, the objectives and expectations of the physical environments quality of the unplanned settlements in Kelurahan Petamburan Village could be identified whether it has referred to eco-settlement and the right strategy or not. Focus of this research is evaluating the variables from the physical environment of eco-settlement. The quantitative descriptive method is expected to be able to evaluate the unit variable conditions of the eco-settlement physical environment, including independent healthy houses, pedestrian ways, waste networks, and natural disaster and fire mitigation response. Ten (10) Neighborhood Units (RT) with 30 respondents are research samples selected at random, representing high, medium, and low density RT Units. Data and information obtain from field observation and interview are processed using The Statistical Product and Service Solutions (SPSS) Program. The results of the study, shows that factors related to the characteristics of unplanned settlements are in line with the criteria for eco-settlement requirements, in the sense of the social aspect, that is institutionalized voluntary self-help-communities or community participatory. This social aspect can be developed to increase further improvement or development of the physical environment.